Baricitinib for the treatment of rheumatoid arthritis - Ivan Urits (Termedia Publishing House, 2020)
Rheumatoid arthritis (RA) is a common inflammatory disease with several implications on health, disability and economy. Conventional treatment for RA centers on anti-inflammatory drugs and specific targeting of tumor necrosis factor  (TNF-) and interleukin 6 (IL-6). Baricitinib is a novel, Food and Drug Administration (FDA) approved, once daily oral drug that is effective in combination with current treatment and results in significantly reduced symptoms with good safety profile. Further studies are required to find rare side effects and evaluate the long term efficacy in disease modulation and patient symptom reduction. This is a comprehensive review of the literature on baricitinib for the treatment of RA. This review provides an update on the pathophysiology, diagnosis and conventional treatment of RA, then proceeds to introduce baricitinib and the data that exists to support or refute its use in RA. The presented study also indicated clinical trials confirming the effectiveness of baricitinib in this indication.